The Influence of Promotions and Ticket Prices on the Decision to Buy Tickets for the Ni Halak Hita 2025 Concert Event - Siregar, Chyntia Brenda Clarissa; Nasution, Harris Pinagaran (Journal of Economics and Social Sciences (JESS), 2025)
Pesta Ni Halak Hita is a cultural music concert organized by Hyga Production on May 31, 2025, at TD Pardede Hall, Medan, aiming to reintroduce Batak Toba culture to the public, particularly younger generations. Amid the growing trend of modern music concerts in Medan, this event offered a distinct concept by showcasing traditional Batak values and featuring Batak artists performing songs in the local language. This study aims to examine the influence of promotion and pricing on consumers' ticket purchasing decisions for the concert. A quantitative descriptive approach was used, with data collected from 97 respondents and analyzed through multiple linear regression, t-tests, and F-tests. The results show that both promotion and price have a positive and significant effect on purchasing decisions, both partially and simultaneously. The t-test results indicate significance values < 0.001 with t-counts greater than the t-table, while the F-test shows an F-count of 15.024 > F-table of 3.09. The Adjusted R-Square value of 0.566 indicates that 56.6% of the variation in purchasing decisions can be explained by promotion and price variables, while the remaining 43.4% is influenced by other factors not examined in this study. These findings highlight the importance of effective promotional strategies and appropriate pricing in increasing consumer buying interest, especially for cultural-based concert events.